2022
DOI: 10.3389/fphar.2022.849006
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Synergistic Antibiotic Combinations by Graph Learning

Abstract: Antibiotic resistance is a major public health concern. Antibiotic combinations, offering better efficacy at lower doses, are a useful way to handle this problem. However, it is difficult for us to find effective antibiotic combinations in the vast chemical space. Herein, we propose a graph learning framework to predict synergistic antibiotic combinations. In this model, a network proximity method combined with network propagation was used to quantify the relationships of drug pairs, and we found that synergis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…We attributed this to their different activity against penicillin-binding proteins . In the previous studies, we found that drugs combinations binding to different targets (e.g., penicillin-binding protein 1a, penicillin-binding protein 1b) of the same biological process (e.g., cell wall) facilitated the bypassing of redundant biological mechanisms, resulting in synergistic effects. Interestingly, we found that ciprofloxacin is classified into Cluster 3 (cell wall inhibitors dominate).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…We attributed this to their different activity against penicillin-binding proteins . In the previous studies, we found that drugs combinations binding to different targets (e.g., penicillin-binding protein 1a, penicillin-binding protein 1b) of the same biological process (e.g., cell wall) facilitated the bypassing of redundant biological mechanisms, resulting in synergistic effects. Interestingly, we found that ciprofloxacin is classified into Cluster 3 (cell wall inhibitors dominate).…”
Section: Resultsmentioning
confidence: 90%
“…However, the method is time-consuming and labor-intensive. In recent years, with the development of high-throughput screening and artificial intelligence, researchers have developed many computational models (e.g., network-based model, , machine learning-based models , ) for predicting DDI, and more details can be found in our previous review . In this study, we focused on unsupervised learning models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the employment of transformers and pre-trained models [62,63], alongside the utilization of propagative network architectures [64], is prevalent for the purpose of feature extraction. It is important to note that the size of the dataset and careful adjustment of model parameters are crucial when using these methods.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Zou et al (Zou et al, 2012) used these topological parameters to explore the underlying mechanisms of drug combinations. Networkbased proximity (Cheng et al, 2019;Lv et al, 2022) can also be used to measure the relationship of two drugs. Based on the ACDB, comprehensive studies of antibiotic combinations at the system level can be undertaken.…”
Section: Investigate Mechanisms Of Antibiotic Combinations Based On N...mentioning
confidence: 99%